HTLV-1 CTCF-binding site is dispensable for in vitro immortalization and persistent infection in vivo - Martinez, Michael P. (Retrovirology, 2019)
BACKGROUND: Human T-cell leukemia virus type 1 (HTLV-1) is the etiologic agent of adult T-cell leukemia/lymphoma (ATL) and the neurological disorder HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP). The exact mechanism(s) through which latency and disease progression are regulated are not fully understood. CCCTC-binding factor (CTCF) is an 11-zinc finger, sequence-specific, DNA-binding protein with thousands of binding sites throughout mammalian genomes. CTCF has been shown to play a role in organization of higher-order chromatin structure, gene expression, genomic imprinting, and serve as a barrier to epigenetic modification. A viral CTCF-binding site (vCTCF-BS) was previously identified within the overlapping p12 (sense) and Hbz (antisense) genes of the HTLV-1 genome. Thus, upon integration, HTLV-1 randomly inserts a vCTCF-BS into the host genome. vCTCF-BS studies to date have focused primarily on HTLV-1 chronically infected or tumor-derived cell lines. In these studies, HTLV-1 was shown to alter the structure and transcription of the surrounding host chromatin through the newly inserted vCTCF-BS. However, the effects of CTCF binding in the early stages of HTLV-1 infection remains unexplored. This study examines the effects of the vCTCF-BS on HTLV-1-induced in vitro immortalization and in vivo viral persistence in infected rabbits. RESULTS: HTLV-1 and HTLV-1∆CTCF LTR-transactivation, viral particle production, and immortalization capacity were comparable in vitro. The total lymphocyte count, proviral load, and Hbz gene expression were not significantly different between HTLV-1 and HTLV-1∆CTCF-infected rabbits throughout a 12 week study. However, HTLV-1∆CTCF-infected rabbits displayed a significantly decreased HTLV-1-specific antibody response compared to HTLV-1-infected rabbits. CONCLUSIONS: Mutation of the HTLV-1 vCTCF-BS does not significantly alter T-lymphocyte transformation capacity or early in vivo virus persistence, but results in a decreased HTLV-1-specific antibody response during early infection in rabbits. Ultimately, understanding epigenetic regulation of HTLV-1 gene expression and pathogenesis could provide meaningful insights into mechanisms of immune evasion and novel therapeutic targets.